Emerging Opportunities for Halal Tourism in Rural Areas: Insights from Indonesia - Mafudi Mafudi; Sugiarto Sugiarto; Agung Praptapa (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2021)
Muslim-oriented tourism has raised international interest, leading to the need to deepen and expand current research into the long-defeated relationship between Islam and geographic tourism. Indonesia was among Muslim-dominated countries encouraging tourism and improving its capacity to host mainly Western visitors. This study explores the feasibility of developing ecological tourism in rural areas – one of Indonesia's leading destinations – about the possibility of building a tourism industry closer to the needs of Muslim customers and more compatible with Islamic beliefs. The study employed qualitative approach. Data analysis performed using an interactive approach which consist of three stages: data reduction, data presentation, and verification/conclusion drawing. This study shows four potentialities for religious education visits: pilgrimage simulation route, Muslim swimming pools, prayer building, and archery venue. Meanwhile the inhibiting factors include accessibility, distance, alliances, and formal structures. SWOT analysis resulted into four strategies that might be useful guideline for the local government in promoting the halal eco-tourism in the rural areas.